Crack widths in base restrained walls subjected to restraint loading - Gottsäter, Erik; Johansson, Morgan; Plos, Mario; Larsson Ivanov, Oskar (Engineering structures, 2019)
•An FE-model for analyzing cracking in base restrained walls is developed.•The model is verified by comparing with previously performed full scale tests.•The model can be used to investigate crack widths due to restraint effects. Cracks in concrete structures can have a negative impact on durability and aesthetic appearance. It is therefore important to estimate crack widths before construction, and to use suitable reinforcement amounts to limit crack widths. Crack widths are however hard to predict in restrained structures, as cracking reduces the stiffness, which in turn reduces the restraint and thereby the amount of cracking. In this paper, nonlinear finite element analyses of cracking are performed on base restrained walls mainly subjected to shrinkage. A non-linear material model for concrete and a bond-slip relation for concrete – reinforcement interaction are used. The model does not include the hardening process of concrete but instead applies the load effects on mature concrete, and is validated by comparisons with test results from full scale tests performed in previous research. Additionally, a sensitivity study is made to investigate the influence of certain parameters on crack widths and crack patterns. The intention is to use the model in the development of a model to be used in design of concrete structures which takes restraint effects into account in an improved, yet a simplified way. The results show that the model gives realistic crack patterns, but that it tends to overestimate crack widths and the number of cracks obtained. Therefore, the model is considered to be acceptable.